Unravelling the Nexus: Exploring the Relationship Between Various Factors and E – Government: A Case Study of Uganda - NAMBASSA, GLORIA; SUSWANTA, SUSWANTA (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
This study investigates the relationship between various factors and e-government adoption in Uganda, employing a case study approach. The results of hypothesis analysis reveal mixed findings. Hypotheses concerning the relationship between Culture (BUD) and E-Government (EGOV) (0.168), as well as between Infrastructure (INF) and E-Government (0.151), are both rejected, indicating an absence of significant associations. Similarly, the hypothesis regarding the relationship between Human Resources (HR) and E-Government (0.066) is rejected, suggesting a lack of substantial correlation between the two variables. However, the hypothesis concerning Information and Communication Technology (ICT) and E-Government(0.006) is accepted, indicating a significant relationship between ICT and E-Government adoption, The discussion highlights the nuanced relationship between cultural factors and e-government adoption, suggesting that while cultural norms may influence citizen engagement with digital governance platforms, the impact varies across contexts. Conversely, the robust positive coefficients associated with infrastructure underscore its critical role in facilitating e-government initiatives. This emphasizes the importance of investing in ICT infrastructure to overcome barriers to e-government adoption in Uganda. The interplay between cultural factors and infrastructure underscores the need for a comprehensive approach addressing both aspects to foster effective e-government implementation in the country. R square in this result is 0.874. An R-squared value of 0.874 indicates that 87.4% of the variance in e-government adoption is explained by the model's predictors, suggesting a strong relationship and high explanatory power. This implies that the model effectively captures key factors influencing e-government adoption in Uganda.